NATIVE GOLD DEPOSITS FROM GAS EMANATIONS OF CINDER CONES PRODUCED BY THE 1975-1976 GREAT TOLBACHIK FISSURE ERUPTIONS - Vergasova L.P.; Starova G.L.; Serafimova E.K.; Filatov S.K.; Filosofova T.M.; Dunin-Barkovskii R.L. (My University, 2001)
Occurrences of recent native gold deposition were discovered around fumarole vents in the craters of the Northern Group of new Tolbachik volcanoes that had been born in 1975-1976. The newly deposited minerals are vertically zoned in accordance with the rise of volatiles, the enrichment of rocks in them, and the deposition of native gold minerals. Gold was identified by microscopic, X-ray, and microprobe analyses. Conditions of native gold accumulation in fumarolic deposits are discussed.